Covid-19 Positive Antenatal Patients in Obstetrics and Gynea Unit, Peshawar - Rabeea Sadaf; Muhammed Zahid; Nasreen Kishwar; Umaiyma Farhad; Behzad Khan Khalil (Gandhara University, 2021)
OBJECTIVES: The study aimed to determine the frequency of COVID-19 positive antenatal patients admitted in Obstetrics & Gynecology unit Hayatabad Medical Complex Peshawar with the concerns that pregnant women may be more susceptible to COVID-19 as they may be more vulnerable to respiratory infection. METHODOLOGY: This was a descriptive cross-sectional study conducted at Obstetrics & Gynecology units Hayatabad Medical Complex Peshawar from May 12th, 2020, to November 29th, 2020, screening and testing of patients admitted for childbirth was in HMC. Screening consisted of questions related to travel, contacts, and symptoms of COVID-19. All patients without a prior diagnosis of COVID-19 underwent SARS-CoV-2 polymerase chain reaction (PCR) testing of nasopharyngeal swabs, with rapid testing available. Patients scheduled for cesarean birth were screened and tested at preoperative visits RESULTS:  One hundred eighty-two patients presenting for antenatal visits were screened; 6.5% (12 out of 182) were previously diagnosed with COVID-19. The remaining 170 patients were tested at admission, and 17.6% (30 out of 170) tested positive for SARS-CoV-2. Twenty-two of the 30 who tested positive for SARS-CoV-2 (73.3%) were asymptomatic. The overall prevalence of positive test results among asymptomatic patients was 14.1% (22 out of 156). The prevalence of positive test results among asymptomatic patients increased from 1.29% (2 out of 155). CONCLUSION: The evidence on this novel infection is changing almost daily, although it will likely be many months before, we can determine the true impact it will have on both maternal and fetal well‐being. In the interim, our primary responsibility is to ensure all women have access to safe maternity services. KEYWORDS: Asymptomatic, COVID-19 Positive, Antenatal Patients, Obstetrics & Gynecology, Infection